2002
DOI: 10.4050/jahs.47.123
|View full text |Cite
|
Sign up to set email alerts
|

Vibratory Loads Reduction Testing of the NASA/Army/MIT Active Twist Rotor

Abstract: Recent studies have indicated that controlled strain-induced hlade twisting can he attained nsingpiezoelectric Active Fiber Composite technology, and that such advancement may provide a mechanism for reduced rotorcraft vibrations and increased rotor performance. To validate these findings experimentally, a cooperative effort between the NASA Langley Research Center, the Army Research Lahoratory, and the MIT Active Materials and Structures Lahoratory has been developed. As a result of this collaboration a four-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 12 publications
(13 reference statements)
2
106
0
Order By: Relevance
“…However, they demonstrated that induced-strain actuation of blade twist was a feasible concept for rotor vibration control. The NASA/ARMY/MIT active twist rotor tested in the NASA Langley Transonic Dynamics Tunnel demonstrated rotor vibratory loads reduction in the fixed frame [10,11]. The active twist rotor of Sikorsky Aircraft also demonstrated 1% to 2% rotor power reduction in wind tunnel tests [12].…”
Section: Introductionmentioning
confidence: 96%
“…However, they demonstrated that induced-strain actuation of blade twist was a feasible concept for rotor vibration control. The NASA/ARMY/MIT active twist rotor tested in the NASA Langley Transonic Dynamics Tunnel demonstrated rotor vibratory loads reduction in the fixed frame [10,11]. The active twist rotor of Sikorsky Aircraft also demonstrated 1% to 2% rotor power reduction in wind tunnel tests [12].…”
Section: Introductionmentioning
confidence: 96%
“…Early experiments on active twist involved changing the twist of the helicopter blade at the root of the blade [2]. Later experiments used a distributed actuation actuation system to modify the blade twist [46,50,58,66]. In a similar manner to the active trailing edge, the placement and the number of actuators modify the amount of vibration that are reduced.…”
Section: Active-twistmentioning
confidence: 99%
“…1) that has been investigated under the Technical Cooperation Program involving the United States, Canada and Australia, (Nitzsche et al, 2001). Other example following in the same category is the Active Twist Rotor (ATR) program that was developed by NASA and other partners in the United States to reduce vibration in helicopter blades (Wilbur et al, 2002;Shin, Cesnik and Hall, 2005). The trailing-edge flap is another example of direct-active concept under investigation for use in rotorcraft to suppress vibratory hub loads and noise.…”
Section: Introductionmentioning
confidence: 99%